2012
DOI: 10.1016/j.jnt.2012.05.022
|View full text |Cite
|
Sign up to set email alerts
|

On the GCD-s of k consecutive terms of Lucas sequences

Abstract: Let u = (u n ) ∞ n=0 be a Lucas sequence, that is a binary linear recurrence sequence of integers with initial terms u 0 = 0 and u 1 = 1. We show that if k is large enough then one can find k consecutive terms of u such that none of them is relatively prime to all the others. We even give the exact values g u and G u for each u such that the above property first holds with k = g u ; and that it holds for all k G u , respectively. We prove similar results for Lehmer sequences as well, and also a generalization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…Later, Ohtomo and Tamari [21] proved that for any coprime integers a, b the arithmetic progression an+b (n ≥ 1) is also a Pillai sequence. Recently, Hajdu and Szikszai [17] together with other related results proved that Lucas and Lehmer sequences of the first kind are Pillai sequences, as well. However, they also demonstrated that being a Pillai sequence is a special property, at least Lucas and Lehmer sequences of the second kind do not have this property in general.…”
Section: Introductionmentioning
confidence: 77%
See 4 more Smart Citations
“…Later, Ohtomo and Tamari [21] proved that for any coprime integers a, b the arithmetic progression an+b (n ≥ 1) is also a Pillai sequence. Recently, Hajdu and Szikszai [17] together with other related results proved that Lucas and Lehmer sequences of the first kind are Pillai sequences, as well. However, they also demonstrated that being a Pillai sequence is a special property, at least Lucas and Lehmer sequences of the second kind do not have this property in general.…”
Section: Introductionmentioning
confidence: 77%
“…The coincidence of these parameters seems to be a common behavior; see [16] and [17] for related situations. However, we are pretty sure that there are elliptic divisibility sequences B with g B < G B , similarly to the cases considered in [16] and [17].…”
Section: Remarkmentioning
confidence: 95%
See 3 more Smart Citations